PENGARUH KEPEMIMPINAN DAN KEDISIPLINAN KERJA TERHADAP PRODUKTIVITAS KERJA DAN DAMPAKNYA PADA KINERJA KARYAWAN PT. SIER. SURABAYA - Riyayah, Riyayah; Purwanto, Purwanto; Rahayu, Sri (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
HR management that regulates a person according to applicable standards provides a sense of justice for those involved. The sense of belonging to the organization also increases, so that leadership and discipline as well as high work productivity can improve employee performance. The purpose of this study was to examine the effect of management and work discipline simultaneously and partially on work productivity and its effect on employee performance at PT. SIER Surabaya. The sample of this research is 96 employees from all parts of PT. SIER Surabaya. Data collection techniques were carried out through observation, distributing questionnaires, interviews and literature study. Analytical methods and path analysis with SPSS version 25 for Windows. The result of the coefficient of determination (Adjusted R2) of 0.788 for the dependent variable of labor productivity means that the percentage of influence of leadership and work discipline on labor productivity is 78.8%. The coefficient of determination of the dependent variable on employee performance is 0.738, meaning that the influence of leadership, work discipline and work productivity on employee performance is 73.8%. The conclusion of this study is that an increase in employee performance is achieved by increasing leadership skills, work discipline and work productivity. Suggestions for PT. SIER Surabaya to provide an example of good leadership to employees and encourage employee discipline to increase work productivity and employee efficiency at PT. SIER Surabaya